Study of thermal behaviour of roofing on subtropical climate: the use of radiant barrier - Teixeira, Carla Fernanda Barbosa (2013)
Solar radiation is the main energy source and responsible for heat gain in buildings, particularly in tropical climate regions. In general, roofing is one of the constructive components that receive most of incident solar radiation in single-storey buildings. One of the techniques to attenuate the solar heat gain is the use of radiant barrier in the roofing system. This paper presents results about thermal performance of different kinds of radiant barrier applied to tiles to verify the temperature attenuation. The study was performed in test cells, where the radiant barrier (aluminum film) was applied to a roofing system consisting of metallic tiles and PVC membrane. Results show that radiant barriers are efficient in providing a good thermal performance of roofing systems and are expected to contribute for the knowledge transfer to designers so as to provide thermal comfort and energy saving in buildings.